Cultural Ties and the Challenge of Ethnic Politics in Contemporary Nigeria; A Study in Historical Origins (Global Journal of Human-Social Science, 2014)
The Challenges of conducting and having a free, fair and credible elections in Nigeria have become daunting. The issue of ethnic politics is undoubtedly, one of these challenges. Thus, the concept of ethnicity and politics in Nigeria is crucial in the analysis of Nigeria's political development in the colonial and post-colonial period. The character of the nationalist movements which later lost its initial unity of direction to factional pressures and the emergence of the Federal principle that was reinforced by the evolution of separatist and regional outlooks had their foundations in the intrusion of ethnic considerations into practical politics. This paper examines the beginnings of the politicization of ethnicity in Nigeria and the role that cultural ties can play in improving it. The work relies on primary and secondary data for its analysis. The secondary data were subjected to textual and contextual analysis albeit adopting the historical method that involves the collection and interpretation of data. The study shows that ethnicisation of politics in Nigeria predates the often emphasized crisis within the Nigerian Youth Movement in 1941 by scholars and that cultural ties and even organisations like mosques, churches and officials of different religious and belief systems working together, could be used to integrate the various ethnic groups while maintaining their identities, as ways out of the ethnic politics 'nightmare'.
Keywords: cultural ties; challenge; ethnic politics; historical origin and nigeria